Factors affecting irrigation management decision-making : the case of Taung Irrigation Scheme in North West Province of South Africa - Stevens, Joseph Benjamin (University of Pretoria, 2021)
Dissertation (M Agric (Agricultural Extension))--University of Pretoria, 2021.